2013
DOI: 10.1371/journal.pone.0081494
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Smooth Muscle Cells of Asthmatics Promote Angiogenesis through Elevated Secretion of CXC-Chemokines (ENA-78, GRO-α, and IL-8)

Abstract: BackgroundAirway wall remodelling is a key pathology of asthma. It includes thickening of the airway wall, hypertrophy and hyperplasia of bronchial smooth muscle cells (BSMC), as well as an increased vascularity of the sub-epithelial cell layer. BSMC are known to be the effector cells of bronchoconstriction, but they are increasingly recognized as an important source of inflammatory mediators and angiogenic factors.ObjectiveTo compare the angiogenic potential of BSMC of asthmatic and non-asthmatic patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…ENA‐78 (epithelial neutrophil‐activating peptide 78 or CXCL5) is a small neutrophil chemo‐attractant cytokine being normally produced as a result of inflammatory stimulation. ENA‐78 was also reported to have potential in regulation of angiogenesis . This finding is consistent with the previous data regarding TCs involvement in (neo)angiogenesis in heart .…”
Section: Discussionsupporting
confidence: 91%
“…ENA‐78 (epithelial neutrophil‐activating peptide 78 or CXCL5) is a small neutrophil chemo‐attractant cytokine being normally produced as a result of inflammatory stimulation. ENA‐78 was also reported to have potential in regulation of angiogenesis . This finding is consistent with the previous data regarding TCs involvement in (neo)angiogenesis in heart .…”
Section: Discussionsupporting
confidence: 91%
“…Previously, we showed that BSMC isolated from asthma patients exhibit increased angiogenic potential, which associated with increased productions of CXCR2 ligands (ENA78, GRO-a and IL-8) and VEGF [37]. Our present study showed that hypoxia predominantly induced VEGF and IL-6, whereas IL-8 was only 2fold increased and ENA-78 not affected.…”
Section: Discussionsupporting
confidence: 57%
“…However, attempts to delve further into the mechanisms of airway angiogenesis and the pathophysiology of angiogenic vessels in asthmatic subjects are limited. Culture medium from airway smooth muscle biopsied from asthmatics and grown in vitro has been shown to cause endothelial cell tube formation in assay systems [25,26]. These studies suggest that a number of common growth factors such as VEGF-A, angiopoetin, IL-8 are all capable of stimulating microvessel growth in vitro.…”
Section: Discussionmentioning
confidence: 99%